Legal Uncertainty in Criminal Cases Termination Institute Enforcement in Connection with Reconciliation of the Parties - Zabuga E. E. (Vestnik Omskoj Ûridičeskoj Akademii, 2014)
The author analyzes the judicial application practice of the RF Criminal Code, Art. 76, of the RF Criminal Procedure Code (in criminal cases involving crimes small and moderate), Art. 25; some procedural problems are designated.